Design and implementation of an inverter control circuit for residential wind generator - Ahmad Firdaus Ahmad Zaidi (Kulliyyah of Engineering, International Islamic University, 2010)
Current utilization level of wind power as alternative source of energy particularly electricity in Malaysia is very low. Some sites particularly coastal and hilly areas have low but steady wind energy supply that is potential to generate electricity for residential use. There is urgent need to locally develop the low cost wind turbine generator for residential use. Recent developments of power electronic converters and embedded computing allow improvement of power electronic converter devices that enable integration of microcontrollers in its design. This has made possible: more flexible control and stable output in respect to nature of wind dynamics, enhanced power extraction and low total harmonic distortion (THD), attributes needed for good quality electrical supply is achievable at lower cost. In this project, an inverter circuit with suitable control scheme design was developed. The circuit was to be used with a selected topology of Wind Energy Conversion System (WECS) to convert electricity generated by 500W direct-drive permanent magnet type wind generator which is typical for residential use. From single phase AC output of the generator, rectifier circuit is designed to convert AC to DC voltage. Then DC-DC boost converter was used to step up the voltage to a nominal DC voltage suitable for domestic use. The proposed inverter then will convert the DC voltage to sinusoidal AC. The duty cycle of sinusoidal Pulse-Width Modulated (SPWM) signal controlling switches in the inverter was generated by microcontroller PIC16F877A. The lab-scale experimental rig involves simulation wind of wind generator by running geared DC motor coupled with 500W wind generator where the prototype circuit was connected at generator output. Experimental circuit produced output voltage single phase 240V sinusoidal AC voltage with frequency of 50Hz. This output complied nominal grid voltage of 240V +5% and -10% and frequency of 50Hz as per requirement by Malaysian Standard MS406:1996. Measured total harmonics distortion (THD) of the voltage across load was 4.0% which is within limit of 5% as recommended by IEEE Standard 519-1992.